Social Marketing Strategy of Frozen Semen Produced by Singosari Artificial Insemination Center - Prafitri, Rizki; Kuswati; Marliana, Dina; Khaerunnisa Firdaus Sadikin; Lensa Auliati (ANIMAL PRODUCTION, 2025)
The research conducted at the Singosari Artificial Insemination Center aims to analyze internal and external environmental factors affecting frozen semen marketing and formulate effective marketing strategies. Using a quantitative explanatory approach, data were collected through observations, interviews, and documentation. Internal factors were evaluated using the Internal Factor Evaluation (IFE) matrix, external factors were assessed through the External Factor Evaluation (EFE) matrix, and the Internal-External (IE) matrix was utilized to determine the company's position, providing a more comprehensive overview of the analysis. Results show that strengths (score: 1.77) and opportunities (score: 1.69) outweigh weaknesses (score: 1.52) and threats (score: 1.4). BBIB Singosari's key strengths include ISO- and SNI-certified frozen semen, genetic diversity, and competitive pricing. Meanwhile, threats such as reproductive diseases and market competition must be addressed. The marketing strategy, based on the SWOT matrix, emphasizes consistent product quality improvement, utilization of market intelligence, and fostering consumer relationships. A significant component of this strategy is social marketing, which raises awareness about artificial insemination and the benefits of high-quality frozen semen. Social marketing involves targeted education through social media, direct farmer outreach, and community campaigns, ensuring higher adoption rates of artificial insemination technology. These strategies strengthen BBIB Singosari's market position while contributing to sustainable livestock population growth in Indonesia. The investigation emphasizes the necessity of innovative marketing approaches to overcome internal and external challenges and enhance BBIB's role as a leader in livestock development.